ASPEK KOMUNIKASI INTERPERSONAL LAYANAN REFERENSI MELALUI SMS DI PERPUSTAKAAN NASIONAL: ANALISIS ISI KUALITATIF - Arief Wicaksono (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2016)
Interpersonal communication is one of keys to success in reference services. This aspect of is required both in conventional and virtual reference services. Short Message Service (SMS) is a way of communication that can be used in virtual reference services. However, using SMS in virtual reference service is not common in Indonesian libraries. The National Library of Indonesia is the only library that use SMS in their reference services. This study is aimed at gaining in-depth knowledge about interpersonal communication aspect that is developed through SMS reference service of the National Library of Indonesia. Categories used in this study are facilitator and barrier relation aspects applied by Radford on the virtual reference service through live chat. The method used is a qualitative content analysis. This study shows that both facilitator and barrier relation aspects are found during the reference transactions. Therefore, it is found that interpersonal communication aspect is highly featured in virtual reference service. SMS can be an alternative for virtual reference service.